Proposal of a new method for strength evaluating of construction of railway vehicles - Tomek, Petr; Středová, Doubravka (Springer, 2017)
This article presents two methods for evaluating the strength of the hood of railway locomotives. The hood is subject to the European standards for railway applications EN 12663-1 Railway applications Structural requirements of railway vehicle bodies Part 1: Locomotives and passenger rolling stock. Czech Standards Institute (2010). The first method is based on the European standard for railway applications EN 12663-1 Railway applications Structural requirements of railway vehicle bodies Part 1: Locomotives and passenger rolling stock. Czech Standards Institute (2010). This method is based on the principle of evaluation of the pseudo-elastic stress. The second method uses the results of geometrically and materially nonlinear numerical analyses. The second method is based on the knowledge of modern science and technology. Structural strength is then evaluated from the real limit state. Using both methods for strength evaluating is shown in this paper (strength evaluation of hood of diesel electric locomotive). The original construction of the hood is analyzed in the first part of this paper. Structural changes are proposed in the next part of this article. The carrying capacity of the new construction of the hood is verified by a numerical analysis. The results of the new construction are compared with the original construction of the hood
Návrh nové metodiky pro vyhodnocení pevnosti konstrukce železničních vozidel
Keywords: Limit state of plasticity · Railway applications · FEM · Strength evaluation